Effects of Square Body Openings in Castellated Steel Beams on Stiffness and Natural Frequencies - Nugroho, Guntur; Aughitri, Fayza (Universitas Negeri Yogyakarta, 2026)
Castella beams are one of the steel structural innovations that have the advantage of reducing weight without sacrificing bending stiffness, so they are widely used in long-span structures. This study aims to analyze how square-shaped openings affect the natural frequency of castellated beams, considering different numbers of openings and various support conditions. The research was conducted numerically using Abaqus CAE software and theoretically using Stokey's theory. Five models were tested with the number of openings between 9 and 19 and three different support conditions: fixed-fixed, fixed-pinned, and pinned-pinned. Results show that increasing the number of openings significantly decreases the mass and stiffness of the beam, which impacts the natural frequency values of the structure. The analysis results using Stokey's theory yield natural frequency values that tend to be higher than the numerical analysis because it does not consider the local weakening effect due to the openings. The difference between the results of the two approaches reaches 7-904 Hz, depending on the configuration and vibration mode analyzed. The difference is more striking at higher vibration modes because the concentration of local deformation is more dominant. Modifying Stokey's formula by adding an inertial correction coefficient proved to predict the downward trend of the natural frequency more accurately. The results show that the natural frequency values at low vibration modes are in high agreement. Therefore, it is recommended to use this approach, especially in low-vibration mode analysis.